`(cot^2 (x) -1) / (1+cot^2 (x)) = (1- 2sin^2 (x))`

We know that: `cotx = cosx/sinx`

`==> ((cos^2 x)/(sin^2 x) -1)/(1+(cos^2 x)/(sin^2 x)) = 1- 2sin^2 x`

`Now we will use common denominator.`

`==> ((cos^2 x - sin^2 x)sin^2 x)/((sin^2 x+cos^2 x)(sin^2 x)) = 1- 2sin^2 x`

Now we will reduce `sin^2 x ` and substitute `sin^2 x + cos^2 x = 1`

`==> cos^2 x - sin^2 x = 1- 2sin^2x`

Now we know that `sin^2 x + cos^2 x = 1 ==> cos^2 x = 1- sin^2 x.`

`==> (1-sin^2 x) - sin^2 x = 1- 2sin^2 x`

`==> 1- 2sin^2 x = 1- 2sin^2 x`

``

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now